Encontros: a insurgência do lugar - Helena Castellain Barbosa de Castro (2016)
This work regards the very serious urban land conflict involving three urban occupations: Rosa Leão, Esperança and Vitória. Located in the northern part of the municipality of Belo Horizonte (Minas Gerais, Brazil), occupants, by implementing the constitutional right to housing, transform the gigantic green area of the Izidora region, until recently ignored by private interest, in a place. During the research, the search for the social suffering experienced by the occupants, however, unfolds in the encounter with happiness, which was called social happiness as a proposal-antithesis to social suffering. In this way, inspired by theprerogatives of science-knowledge and the instigated process of building alternatives to dialogue, the methodology is redefined along the trajectory a process of learning. Along with this path, as light beams through gaps of the wall, the specific spaces-times of life developed in the Izidora occupations, it ignites dreams of change while illuminating the image (possible object) of urban-utopia. Thus, it is presented the encounter with social suffering using black-and-white photos, representing the neoliberal urban space (homogeneous, alien to life, the horizon of the capitalist space project). Already in the ambit of social happiness, colored, the figures express the encounter with the place (heterogeneous, in favor of life, the horizon of the alternative space project). Social happiness, in fact, rooted in place and satisfied only by it, would be part of the flow of thought waves for the right to other cities revolutionary happiness.